MENAKAR BAHASA DALAM SASTRA: PERBINCANGAN SEPUTAR TATA BAHASA DAN SASTRA - Jejen Jaelani (Fakultas Seni Rupa dan Desain ITB, 2011)
Grammar plays an important role as a foundation for writing activities. However, many people who feel reluctant when hearing the phrase